The Sweden Democrats and the ethno-nationalist rhetoric of decay and betrayal (Sociologisk Forskning, 2017)
Sweden was long considered an ”exceptional case” with no representatives of the radical right in parliament. However, the Sweden Democrats (SD) entered parliament in the 2010 parliamentary election, pointing towards the demand for ethnic nationalism also in Sweden. This article explores the party’s rhetoric with particular references to the politics of decay and betrayal and its construction of a Swedish golden age. The rhetoric of decay echoes the ethnicity-based nationalisms articulated in other parts of Europe alongside nationalist claims of homogenous origins, a common destiny and an inherited social solidarity. The empirical material consists of political election programs since 1989 (SD 1989), high profile speeches and the party journal (SD Kuriren).